Motivation of Undergraduate Petroleum Engineering Student of Bandung Institute of Technology Towards Geothermal Energy as Career Choice (Journal of Business and Management, 2022)
In recent years, the world is facing a global issue related to the sustainability of sustainable life in the future. Various campaigns and programs have begun to be realized in order to maintain the global ecosystem, one of which is by reducing the use of CO2-emitting fuels or also known as fossil fuels. Reducing the use of fossil fuels must of course be substituted in other forms of energy, one of which is renewable energy. Based on the geological conditions of Indonesia, geothermal energy is a renewable energy that has great potential for its development in Indonesia. Of course, the development of geothermal energy requires skilled human resources in this field. Here the researcher makes the students of the Bachelor of Petroleum Engineering Bandung Institute of Technology as research subjects. Students as the next generation in this industry certainly need to prepare skills and knowledge for this opportunity. For that, of course, it takes motivation as an individual mover. Motivation also has a dynamic form and is highly personalized by environmental conditions. In the definition of motivation, each individual has control over himself and has the right to make choices in deciding to make an effort to try to achieve individual goals. This study uses a quantitative approach to collect data from respondents. In this study, each respondent was given 18 questions, which were representative of 5 variables from Maslow Hierarchy of Needs Theory. In this research, it was found that the motivation of the students of petroleum engineering at the Bandung Institute of Technology to see geothermal energy as a career choice is already at a high level.Keywords: Motivation, Geothermal Energy, Renewable Energy, Maslow’s Hierarchy of Theory, Career Choice, Students